FACTORS RELATED TO THE QUALITY OF HANDOVER OF SITUATION, BACKGROUND, ASSESSMENT, RECOMMENDATION (SBAR) METHODS ON INTERNAL PATIENT TRANSFER - Tri Ismu Pujiyanto; Salvania Ermi Wahyuningtyas; Dwi Kustriyanti (Jurnal SMART Keperawatan, 2024)
Communication errors are one of the causes of patient safety incidents. Handover of internal patient transfers using the SBAR methodis a form of communication whose implementation has not been carried out optimally. Purpose: To determine the factors associatedwith the quality of the SBAR handover method in internal patient transfers. Research method: Type of correlational quantitativeresearch. Cross-sectional research design. The population consisted of 94 nurses who carried out internal patient transfers. Thesample consisted of 76 nurses who transferred level 0 patients. The sampling technique uses purposive sampling. Measuring toolsuse questionnaires and observation sheets. Statistical tests use the Chi-Square test. Results: Nurse attitude (P-value = 0.000) andOdds Ratio 8.543, receive motivation (P-value = 0.003) and Odds Ratio 5.315, Head of Space leadership (P-value = 0.001) and OddsRatio 6.367, and head of room supervision (P-value = 0.002) and Odds Ratio 5.769. has a P-value of <0.005, using Chi-Square Testanalysis and Logistic Regression to see the most influential variable, nurse attitude.  Conclusion: The attitude sub-variable is the mostinfluential on the quality of SBAR method handover in internal patient transfer. Suggestion: Hospitals must conduct periodic andcontinuous evaluations of handover activities. The nurse's attitude that needs to be improved is the understanding of the sta ges andadjustment of the appropriate internal transfer time of the patient.